Long QT Interval Syndrome and Female Sex—Review and Case Report - Lana Maričić; Livija Sušić; Damir Mihić; Nikolina Šego (Reports)
Background and Clinical Significance: Congenital LQTS is a life-threatening condition, resulting from a mutation of the gene encoding the cardiac ion channels, which results in prolongation of the ventricular action potential. Genetic screening of family members in symptomatic and asymptomatic patients is crucial for the prevention of sudden cardiac death. There are a number of detected mutations of congenital LQTS, of which the three forms LQT1, LQT2, and LQT3 are the best described. In addition to the described ECG morphology, the key triggers and treatment approach are described. This emphasizes even more the importance of timely screening of these patients, and the decision for therapy. It should be emphasized that the phenotypic manifestations significantly depend on the affected genes. The guidelines in the treatment approach are very clear, although it should be emphasized that beta blockers are the first and basic treatment therapy. The therapeutic choice is narrowed especially if they are not effective. Case Presentation: This is a case report of a young woman diagnosed with LQTS who was confirmed to have KCNH2 mutations through genetic analysis. The same mutation was also confirmed in her children. Changes in the therapeutic approach are described, and the use of beta blockers, depending on the symptoms and drug tolerance. Especially in the postpartum period, due to reduced progesterone levels, in this case, the patient was implanted with a cardioverter defibrillator. Conclusions: It should be emphasized that timely recognition is essential for early diagnosis, regular control, timely initiation of treatment, and prevention of adverse events.